(untitled) (Physical Education, Health and Social Sciences, 2025)
Sindhi Kafi singing is one of the most expressive forms of Sindhi folk and Sufi music, combining poetry, spirituality, and melodic artistry. Its performance relies on traditional musical instruments that not only provide rhythm and melody but also preserve centuries-old musical heritage. Instruments such as Ektaro, Chapri (Khartal), Dholak, Gharo, Sharnai, Bansuri, Sarindo, Banjo, and Tabla have been integral to this art form. Each of these instruments contributes uniquely to the tonal identity and emotional depth of Sindhi Kafi, linking it with both the rural and spiritual life of Sindh. Research Questions: • What are the major traditional instruments used in Sindhi Kafi singing? • How do these instruments contribute to the rhythm, melody, and emotional expression of Kafi? • What transformations have occurred in the use of these instruments over time? • How does modernization influence the preservation and performance of traditional Sindhi instruments? Objectives: • To identify and document the traditional musical instruments used in Sindhi Kafi singing. • To explore the structural and functional role of each instrument in Kafi performance. • To analyze how these instruments support the transmission of Sindh’s spiritual and folk traditions. • To examine the contemporary status of these instruments and the changes in performance practices. Research Methodology:This study employs a qualitative descriptive and historical approach. Primary data were collected through field interviews with folk musicians, observation of live performances, and archival recordings from Radio Pakistan and cultural institutions. Secondary data were drawn from literary sources, research publications, and previous studies on Sindhi music and folklore. The analysis focuses on comparing traditional and modern performance styles to understand the evolution of instruments within Kafi singing. Conclusion:The study concludes that traditional instruments such as Ektaro and Chapri remain central to Sindhi Kafi due to their symbolic and rhythmic significance. However, modernization has gradually introduced new instruments like the Banjo and Tabla, replacing older ones such as Dholak and Sarindo. Despite this evolution, the essence of Sindhi Kafi continues to reflect a deep spiritual connection between music, devotion, and cultural identity. Preserving these instruments is essential for maintaining the authenticity and emotional depth of Sindhi musical heritage.